Analysis Factors Affecting the Demand and Supply of Local Chicken Meat in Pakpak Bharat Regency - Mizanul Akbar; Hasnudi Hasnudi; Tavi Supriana (Budapest International Research and Critics University, 2021)
Food needs are basic human needs that must be met. One of the food needs comes from animal sources, the source of meat most consumed in Pakpak Bharat is local chicken. From the consumer side, the factors that affect the demand for local chicken include: the price of local chickens, the price of tilapia, population and income, and factors that affect the demand for local chicken include: the price of local chicken, the price of local chicken feed and the price of local chicken seeds. The purpose of this study is to analyze the factors that affect the demand and supply of local chickens in Pakpak Bharat Regency in 2010 - 2019, to forecast the production of local chicken in Pakpak Bharat Regency in 2020-2029. Data analysis was performed using the Ordinary Least Square (OLS) method with multiple linear regression estimation models using the help of the SPSS 20 program. The estimation results of the demand model are variables of tilapia meat prices (X2), population (X3), and per capita income (X4) has a positive and significant effect on the demand for local chicken (Y), while the price variable for local chicken meat (X1) has a negative and significant effect on the demand for local chicken meat (Y). The estimation results of the model offer variable price for local chicken meat (X1) have a positive and significant effect on the supply of local chickens (Y), while for the variable price of local chicken feed (X2) and the price of local chicken seeds (X3) have a negative and significant effect on offering local chicken meat (Y). Simultaneously, all variables of the demand and supply of local chicken meat have a positive effect. Resultthe projection trend of local chicken production in Pakpak Bharat Regency in 2020-2029 is a positive trend or has increased every year.